Pengaruh Elemen-Elemen Fraud Pentagon Terhadap Kecurangan Laporan Keuangan - Alfamet Randa; Sany Dwita (Universitas Negeri Padang, 2020)
This study aims to determine the effect of pentagon fraud’s theory in detecting fraudulent financial reporting empirical studies on companies in property and real estate sector in Indonesia listed on the Stock Exchange in 2014-2018. The sampling technique used purposive sampling with the final sample of 18 companies. Data analysis used in this research is logistic regression analysis. The result of this research showed that : Pressure (ROA), Opportunity (BDOUT), Competence (DCHANGE) and Arogance (CEOPIC) have no significant effect on fraudulent financial reporting. While the Rationalization (Change of Auditor) has a significant effect on fraudulent financial reporting.